Prognostic index to assess the risk of systemic right ventricular failure after atrial switch operation for transposition of the great arteries - Giselle Serrano Ricardo; Adel Eladio González Morejón; Mariela Céspedes Almira; Yudith Escobar Bermúdez; Aydee Santamarina Fernández; Tania Rosa González Rodríguez (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2021)
The introduction of atrial switch operation allowed to prolong the life expectancy of those born with transposition of the great arteries. This operation involves extensive surgery in the atria and leaves the right ventricle as the systemic ventricle that develops dysfunction because its anatomy is not intended to handle systemic pressure over a lifetime. We hypothesized that certain echocardiographic variables contribute to the identification of systemic right ventricular failure and accurately predict prognosis in follow-up of these patients. The objective was to desing and validate a prognostic index for the estimation of risk of systemic right ventricular failure after atrial switch operation for transposition of the great arteries. An observational, prospective, cross-sectional study was conducted in 90 patients of the Pediatric Cardio Center "William Soler" from 2011 to 2017. Early systolic dysfunction of the systemic right ventricle was observed, dependent on the increase in afterload. There are no alterations in early diastolic function. The variables that make up the prognostic index are: end-diastolic diameter and parietal thickness of the right ventricle, Right Ventricle Ejection Fraction (RVEF), Tei index, the derivative of pressure over time (dp/dt) and tricuspid regurgitation. The index shows good discriminatory capacity and adequate calibration in prediction of ventricular dysfunction. End-diastolic diameter and parietal thickness of the right ventricle, the derivative of pressure over time and tricuspid regurgitation, demonstrate clinical relevance. The prognostic index shows validity and allows its introduction into clinical practice.